APLIKASI PERAWATAN LUKA DENGAN MENGGUNAKAN ENZYMATIK THERAPY: ALOE VERA DALAM MANAJEMEN LUKA DIABETES - Ferawati Ferawati (Jurnal Ilmiah Kesehatan, 2018)
Introduction:Diabetes mellitus is a metabolic disease group will facilitate the occurrence of diabetic foot wounds. To prevent the complications of diabetic wound that lasts longer and prevents the worse then takes care of wounds in diabetics. Latest wound care techniques are already using a bandage. The principle of modern wound treatment products is to maintain and keep the environment humid permanent cuts to facilitate the process of wound healing, maintaining the loss of fluid networks and cell death. Objective: this study aimed to find out how the application methods of wound care using the enzymatik therapy: aloe vera in diabetic wound management. Methods: the study was qualitative research with approach case studies, a number of participants 1 person: patients with diabetic wounds, treated for 9 days using the method of modern wound care therapy: enzymatic reactions with the use of aloe vera. Participants selected by the method of purposive sampling. Data collection using observation and interviews, data analysis using the method of explanation building. Results: the results of the research there are 4 themes, namely the study of the wound, the kind of wrap used, how to wound care, influence on the wound. The study of the wound using Bates-Jensen Wound Assessment Tool, a type of bandage used are enzymatic reactions therapy: aloe vera and ointments wound, how to wound care using approaches TIME management, and reduced effect on wound care the size of the cuts, epitelisasi, granulation wounds and the amount of fluid that appears. Conclusion: the method of Application wound care therapy: enzymatic reactions using aloe vera on wounds of diabetes affect the dwindling size of cuts, epitelisasi and granulation wound. Health care personnel are advised to use enzymatik therapy: aloe vera in the treatment of diabetic wounds as diabetic wound management integrated with attention to the principles of wound care using the latest evidence based nursing